Metalepsis out of Bounds (ENTHYMEMA, 2013)
This is a review of the panel “Metalepsis out of Bounds” presented at the 2013 ENN conference. The three convenors proposed complementary remarks to the extent that they either questioned the conceptualization, examined the functioning of metalepsis or applied theoretical models to textual material. Beside an in depth reflection upon the concept, broader questions concerning narrative and popular assumptions of narratology arose.
Keywords: Narratology; metalepsis; transfictionality